Reading Othello in Kentucky - Elizabeth Oakes; Heather Adkins; Maggie Brown; Carrie Carman; Gary Crump; Cle'shea Crain; Amanda Hayes; Tara Koger; Mike Sobiech; Chuck Williamson (Journal of the Assembly for Expanded Perspectives on Learning, 2007)
Members of a graduate Shakespeare class at Western Kentucky University discuss Otherness in the context of Othello and national perceptions of Kentucky.